2011
DOI: 10.1111/j.1399-3054.2011.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mitochondrial alternative oxidase expression on the response of Nicotiana tabacum to cold temperature

Abstract: The plant mitochondrial electron transport chain (ETC) includes a non-energy conserving alternative oxidase (AOX) thought to dampen reactive oxygen species (ROS) generation by the ETC and/or facilitate carbon metabolism by uncoupling it from ATP turnover. When wild-type (WT) Nicotiana tabacum grown at 28°C/22°C (light/dark) were transferred to 12°C/5°C, they showed a large induction of leaf Aox1a mRNA and AOX protein within 24 h. Transfer to cold also resulted in a large accumulation of monosaccharides, an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 67 publications
3
79
0
Order By: Relevance
“…1). This correlates well with our previous studies showing that RI29 is the stronger of the two knockdowns (Wang et al, 2011;Wang and Vanlerberghe, 2013;Cvetkovska et al, 2014). In RI29, the effects of drought on A n , ETR II , excitation pressure, F PSII , and NPQ were all strongly magnified relative to the wild type, whereas RI9 (the slightly weaker AOX knockdown) always showed an intermediate response between RI29 and the wild type (Figs.…”
Section: Aox Respiration Provides a Critical Electron Sink Supportingsupporting
confidence: 92%
See 1 more Smart Citation
“…1). This correlates well with our previous studies showing that RI29 is the stronger of the two knockdowns (Wang et al, 2011;Wang and Vanlerberghe, 2013;Cvetkovska et al, 2014). In RI29, the effects of drought on A n , ETR II , excitation pressure, F PSII , and NPQ were all strongly magnified relative to the wild type, whereas RI9 (the slightly weaker AOX knockdown) always showed an intermediate response between RI29 and the wild type (Figs.…”
Section: Aox Respiration Provides a Critical Electron Sink Supportingsupporting
confidence: 92%
“…Transgenic plant lines with suppressed levels of AOX protein (RI9 and RI29) attributable to the presence of an AOX1a RNA interference construct, or elevated levels of AOX protein (B7) due to the presence of an AOX1a transgene driven by a constitutive promoter were previously described (Wang et al, 2011;Wang and Vanlerberghe, 2013;Cvetkovska et al, 2014). In particular, it has been shown that AOX protein levels are strongly suppressed in the knockdowns, even under the strongly AOX-inducing conditions of low temperature (Wang et al, 2011) or severe drought (Wang and Vanlerberghe, 2013). Seeds were germinated in vermiculite for 16 d and then transferred individually to 4-inch plastic pots containing a general purpose growing medium with 4 parts soil (Promix BX; Premier Horticulture) and 1 part vermiculite.…”
Section: Plants and Growth Conditionsmentioning
confidence: 99%
“…Furthermore, the short time (hours) of the cold treatment did not affect lipid peroxidation rates between wildtype and NtAOX1 overexpressing plants. This result does not conflict with the primary role of AOX1 as an ROS scavenger under long periods of cold growth (Wang et al, 2011). After all, the ROS accumulation mechanism and mitochondrial respiration response are distinct between transient and steady stress.…”
Section: Overexpression Of Osaox1a Results In Less Oxidative Damage Umentioning
confidence: 59%
“…Overexpressing AtAOX1 produced better shoot growth at 12°C, whereas shoot growth was significantly inhibited in knockdown plants compared to wild types (Fiorani et al, 2005). In addition, biochemical and molecular changes were also observed in tobacco plants with suppressed or constitutively expressed NtAOX1a, although growth performance was not mentioned (Wang et al, 2011). On the other hand, increasing evidence from different plant species has indicated that the expression of AOX1 or the activity of AOX might be induced by low temperatures, as well as by drought or other abiotic stresses.…”
Section: A B Genetics and Molecular Research 12 (4): 5424-5432 (2013)mentioning
confidence: 96%
See 1 more Smart Citation